Visual intelligence : - Stacey, Mark (John Wiley &​ Sons, Inc., 2013)
The book thoroughly covers the Microsoft toolset for data analysis and visualization, including Excel, and explores best practices for choosing a data visualization design, selecting tools from the Microsoft stack, and building a dynamic data visualization from start to finish.